Therapeutic Potential of Acanthospermum hispidum: A Comprehensive Analysis of Its Antimicrobial, Antioxidant, and Anticancer Properties - Ehssan H. Moglad; Alshaimaa A. Alnoor; Nagla M. Eltayeb; Eshtiyag A. Abdalkareem; Amna Ali; Magbool E. Oraiby; Shahnaz Sultana; Asaad Khalid; Ashraf N. Abdalla (Journal of Spectroscopy)
Acanthospermum hispidum DC. is a plant with extensive traditional use in folk medicine for treatment of various infections in Sudan including jaundice, stomach discomfort, constipation, and viral infections. This research was carried out to explore the biological and chemical properties of the crude extract of A. hispidum. Ethanol crude extract was prepared from the aerial parts of the plant and investigated for antibacterial action against standard monoderm and diderm bacteria using the cup plate method. Free radical scavenging was investigated out by using the DPPH method. Cytotoxicity assay was performed against human breast cancer cell line MCF7 using the MTT assay. Bioactive compounds were identified using GC-MS. The ethanolic extract of A. hispidum revealed antibacterial activity against all the tested bacteria. Also, the extract exhibited potent antioxidant activity at 0.5 mg/ml using DPPH (83% ± 00.09). The cytotoxicity against MCF7 revealed potent growth inhibition activity (IC50 75.8 µg/ml). GC-MS analysis revealed the presence of ethyl α-d-glucopyranoside, hexadecanoic acid, stigmasterol, β-sitosterol, undecanoic acid, phytol, alloaromadendrene oxide, 3-cyclopentylpropionic acid, 2-dimethylaminoethyl ester, and longifolenaldehyde in aerial parts of A. hispidum, all of which support antibacterial, antioxidant, and cytotoxic properties.